Assessment of soil contamination due to oil of gasoline stations - Франчук, Г.М.; Радомська, М.М. (Proceedings of National Aviation University (archive), 2009)
The technique and results of soils pollution with petrochemicals in the vicinity of filling stations of Kyiv are presented on the example of filling stations within Desnyansky and Dniprovsky areas. Based on the analysis of received data the regularities of pollution formation and distribution were defined.